ESSENCE AND PRIORITY OF DIGITAL TRANSFORMATION FOR INTERNATIONAL BUSINESS - Bondar , A.O. (The actual problems of regional economy development, 2023)
It has been established that in today's conditions, a number of domestic entrepreneurs are looking for solutions regarding the restoration of their own business, as well as the prevention of risks arising in the course of the 4th industrial revolution. According to the results of information agencies, by 2030, about a quarter of existing jobs may disappear. At the same time, the most vulnerable specialties are those that can be replaced by digital artificial intelligence and robotics.In addition, the circular economy model is also gaining relevance, namely the recovery of resources, the transition to various clean energy sources, waste processing, and the improvement of medical systems, which has become quite relevant during the exacerbation of the COVID-19 pandemic.Also, the fact of the armed aggression of the Russian Federation against Ukraine significantly affected the global economic environment, due to the redistribution of the sphere of influence of countries in various fields. Every day in the international business environment, a sufficient number of programs, automation tools, communication tools, and service tools are used that optimize the work of business entities in various sectors of the economy. The leaders in the segment of digital transformation are: USA, China, Israel, Japan, Canada, Australia, United Arab Emirates. Each "digital leader" of the international market has its own methods, concepts and "digital strategies" for digital transformation, which are also relevant for the domestic sector. The purpose of the article is to explore the essence and priorities of digital transformation for international business. To achieve the set goal, the article uses: theoretical and methodological provisions of the digital economy, international economic relations, reengineering, and digital management related to the established research problems. The information basis for the dissertation research is international normative and legislative acts, research practices, monographs, publications, analytical reports. The article examines the priority of digital transformation for international business. The basis of the study is the generalization of the essence and content of the concept of "digital transformation", the structure of the processes of digitalization of international economic relations is investigated, schematic processes that occur during the digital transformation are given. The scientific novelty of the study is the updating of existing theoretical and methodological provisions on the digital transformation of international business, as well as the structuring of priorities during digital transformation. The results of the scientific process can be applied to approbation of the international experience of digital transformation of the business environment for domestic subjects of international business.